Larangan Poligami Sebagai Perjanjian Perkawinan Di Tinjau Dari Perspektif Hukum Positif Dan Madzahibul Arba’ah - Alfan Mudzakkir, Muhammad Hasan; Khotibul Umam, M. Nur (Sekolah Tinggi Agama Islam Miftahul Ulum Lumajang, 2023)
This study aims so that community marriages in Kaliboto Village do not misunderstand the prohibition of polygamy as an agreement that is often carried out. And this research was carried out from March to May 2023, taking place in Kaliboto Village, Jatiroto District, Lumajanag Regency. The problem formulation for this research is: 1. Prohibition of polygamy as a marriage agreement in Kaliboto Lor Village, Jatiroto District, Lumajang Regency? 2. Is the prohibition on polygamy as a marriage agreement viewed from a positive legal perspective? 3. The prohibition of polygamy as a marriage agreement viewed from the perspective of madzahibul arba'ah? This research includes the type of field research or qualitative and quantitative. the data in this study were 3 husbands and wives and 1 community leader in Kaliboto Lor Village. data collection techniques used interviews and documentation. data analysis techniques used the KUHAPER book, Compilation of Islamic Law (KHI), and the Book of madzahibul arba'ah with the theory of data reduction, presenting data, and concluding data. The results of this study indicate that: (1) married couples who enter into a marriage agreement in the village of Kaliboto or that solely aim to make the couple sakinah mawaddah warohmah. (2) The positive legal and madzahibul arba'ah perspectives on marriage agreements entered into by married couples in Kaliboto village or contained in Marriage Law No. 1 of 1974 article 29, Government Regulation Number 9 of 1975, compilation of Islamic law and the book of madzahibul arba'ah.